2019
DOI: 10.1039/c8sc04884c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient cell surface labelling of live zebrafish embryos: wash-free fluorescence imaging for cellular dynamics tracking and nanotoxicity evaluation

Abstract: We developed a red-fluorescent stain capable of achieving wash-free plasma membrane imaging in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 54 publications
(44 reference statements)
0
36
0
Order By: Relevance
“…Recent studies demonstrated a close correlation between zebrafish and human pigmentation [9][10][11], with many depigmenting agents identified using zebrafish embryos or larvae [12][13][14][15]. In addition, zebrafish are now used to test several types of drug delivery systems, including liposomes [16,17], micelles [18], and nanoparticles [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated a close correlation between zebrafish and human pigmentation [9][10][11], with many depigmenting agents identified using zebrafish embryos or larvae [12][13][14][15]. In addition, zebrafish are now used to test several types of drug delivery systems, including liposomes [16,17], micelles [18], and nanoparticles [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as shown in Figure A, Pent‐TMP could clearly visualize the boundary of every single cell on the surface of zebrafish, even at large magnifications (Figure B). In contrast, the other commercial PM‐specific dyes, such as DiD and Cell Mask Green, could not exhibit similar results . This may be due to their excessive lipid solubility, which could not penetrate the hydrophilic mucus layer on the surface of zebrafish .…”
Section: Methodsmentioning
confidence: 92%
“…PM imaging plays an important role in biosystems. For example, when the cells are damaged, the morphology of PM changes . Additionally, the PM morphology of erythrocytes in sickle‐cell disease is obviously different from that of people without the disease.…”
Section: Methodsmentioning
confidence: 99%
“…16 Moreover, because zebrafish embryos are transparent, the use of fluorescently tagged transgenes allows the visualization of the development of the neurological systems and the monitoring of neurological disorders in a living organism. 17 The current study aimed to document the potential developmental neurotoxicity of SiO 2 NPs in vivo by taking advantage of the unique features of the zebrafish model. Specifically, the hypothesis was raised that SiO 2 NPs would lead to the underdevelopment of neurological systems in zebrafish by perturbing a specific stage in neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%